(untitled) (Journal of Parents and Teachers, 2014)
Crisis may have made appear “we can’t afford it” opposite to “yes, darling” as an answer to kids’ expectations and demands. This is the best moment to add the familiar economic analysis to class as part of learning for life within a Tutorial Action Plan. There must be a realistic perspective of the economic familiar situation and value reasonably and in an adult way what families can or cannot afford.